No. 7b - 2b = 5b
If you mean: -3*(-2b-3)+7b then it is an algebraic expression that can be simplified to 6b+9+7b = 13b+9
2B Multiplied by 3 plus B = 7B. Here is how it's worked out. You start with 2B, multiply that by 3 and you get 6B. Now all you have to do is add the last B, therefore adding 1B to equal 7B.
It is: 7b+10 simplified
(-3b - 4)(-2b + 5)
The given expression can be simplified to: 3b-a
Collect the terms in a, then the terms in b, getting 6a - 3a + 2b + 5b which simplifies to 3a + 7b. Gettit?
It is an equation and the value of b is 3
7b + 16 = 5b + 247b - 5b = 24 - 162b = 8b = 4
a + 7b + 2c
10a+7b undefined variables cannot be determined
ok, let's see: (3a-2a) + (2b+5b) +(-c +3c) = a + 7b +2c I think that's right.
add like terms: 3a -2a -5b + 6b +3b - 7b = a -3b
20a plus 14 will be 34a minus 8a minus 7 34a minus 8 is 26a minus 7 is 19a. The single b is 1b plus 6b which is 7b minus 2b equals 5b.
4b plus 7b plus 5 will equal 11b plus 5. When you have two variables that are the same you can add the two numbers with the variables remaining the same.
7b-10 = -3
Add 2 to each side: 3b = 7b + 6 Subtract 7b from each side: -4b = 6 Divide each side by 4: -b = 1.5 Change sign: b = -1.5
cosits 7B lol:-)
7b-7 = 0
For graphite pencils the # is the hardness; the letter represents the darkness. 2 is a soft led, 7 hard. B 'should' be black, HB is generally a steel gray, H a little lighter.
Darker-Lighter 9B 8B 7B 6B 5B 4B 3B 2B B HB F H 2H 3H 4H 5H 6H 7H 8H 9H
It is: 19b+7b = 26b
2b + 3 b = 12 . 27 since the beginning is 2 x 12, which equals 24, and then you have to add the extra 3.